Tabela de vida dinâmica para Nauphoeta cinerea (Olivier 1789), Blaberidae, Blattaria - Silva, Anna Clara Balbina; Pelli, Afonso (Ciência e Natura, 2026)
Life tables are used to describe and understand population dynamics studies. The cockroach Nauphoeta cinerea is among the most used species as an alternative model to replace mammalian trials, as they have high reproductive capacity, short life cycle, and low maintenance. This study aimed at developing a dynamic life table for Nauphoeta cinerea, to better understand the biology of this insect. The experiment was conducted with an initial population of 27 individuals, with a specific age group, counted and fed weekly. Reproductive characteristics have been evaluated, and life table was used to estimate the mean generation time (T), net reproductive rate (Ro), intrinsic rate of increase (Rm) and finite rate of increase (λ). The data obtained from the life table indicate that Nauphoeta cinerea has higher initial survival rates, high biotic potential, and good growing capacity under favorable breeding conditions.